2022
DOI: 10.1007/s11224-022-01976-2
|View full text |Cite
|
Sign up to set email alerts
|

Towards the discovery of potential RdRp inhibitors for the treatment of COVID-19: structure guided virtual screening, computational ADME and molecular dynamics study

Abstract: Coronavirus disease 2019 (COVID-19) has become a major challenge affecting almost every corner of the world, with more than five million deaths worldwide. Despite several efforts, no drug or vaccine has shown the potential to check the ever-mutating SARS-COV-2. The emergence of novel variants is a major concern increasing the need for the discovery of novel therapeutics for the management of this pandemic. Out of several potential drug targets such as S protein, human ACE2, TMPRSS2 (transmembrane protease seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, there are no more recent reports related to clinical studies. In the case of the compound DRI-5, in 2022, through SBVS studies, this molecule was proposed as a potential agent to treat COVID-19 targeting SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) [35]. Despite this, in vitro validation still is not demonstrated.…”
Section: Adme Predictionsmentioning
confidence: 99%
“…However, there are no more recent reports related to clinical studies. In the case of the compound DRI-5, in 2022, through SBVS studies, this molecule was proposed as a potential agent to treat COVID-19 targeting SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) [35]. Despite this, in vitro validation still is not demonstrated.…”
Section: Adme Predictionsmentioning
confidence: 99%
“…Successful attempts were made previously by computational studies to find the Repurposing drug molecules in the literature that can efficiently bind to SARS-CoV-2 targets. Among several possible targets, including spike protein, main protease (M pro ), etc., RdRp is a promising target for drug design. Some antiviral molecules have already been identified by targeting key residues in the active site of RdRp and other proteins involved in the lifecycle of the virus. At the same time, various drug repurposing studies that target RdRp using computational tools like docking have also been reported. All of these studies resulted in a great number of possible drugs that could be repurposed for the treatment of COVID-19, pending rigorous theoretical or experimental tests.…”
Section: Introductionmentioning
confidence: 99%